2011
DOI: 10.1021/jp109530f
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Cellular Localization and Binding Preference to RNA, DNA, and Phospholipid Membrane for Luminescent Ruthenium(II) Complexes

Abstract: Because of their unique photophysical properties, sensitively depending on environment, ruthenium dipyridophenazine (dppz) complexes are interesting as probes for cellular imaging with fluorescence microscopy. Here three complexes derivatized with alkyl ether chains of varied length, which exhibit distinctly different cellular staining patterns by confocal laser scanning microscopy, are studied regarding their binding preference for rRNA compared with calf thymus DNA (ct-DNA) and phospholipid membranes. Co-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 46 publications
4
39
0
2
Order By: Relevance
“…This is demonstrated in our work on the hydrophobic dinuclear Ru II tpphz complex [(Ru(DIP) 2 ) 2 (tpphz)] 4 + (DIP = 4,7-diphenyl-1,10-phenanthroline), which, despite possessing an appreciable affinity for DNA in cell-free conditions, targets the membrane-dense endoplasmic reticulum in cells. [58] Similar effects are seen in other studies, including those on prototypical Ru II (dppz) DNA-binding systems [59,60] and cyclometallated Ir III complexes. [61] Both 3 and 4 possess far superior cellular uptake properties than their dinuclear Ru II -Ru II analogue, the effectively isostructural ruthenium analogue 1, [37] indicating that the lower charge of the heterometallic species has facilitated increased cellular uptake rates.…”
Section: Discussionsupporting
confidence: 75%
“…This is demonstrated in our work on the hydrophobic dinuclear Ru II tpphz complex [(Ru(DIP) 2 ) 2 (tpphz)] 4 + (DIP = 4,7-diphenyl-1,10-phenanthroline), which, despite possessing an appreciable affinity for DNA in cell-free conditions, targets the membrane-dense endoplasmic reticulum in cells. [58] Similar effects are seen in other studies, including those on prototypical Ru II (dppz) DNA-binding systems [59,60] and cyclometallated Ir III complexes. [61] Both 3 and 4 possess far superior cellular uptake properties than their dinuclear Ru II -Ru II analogue, the effectively isostructural ruthenium analogue 1, [37] indicating that the lower charge of the heterometallic species has facilitated increased cellular uptake rates.…”
Section: Discussionsupporting
confidence: 75%
“…For example, Matson and coworkers synthesized a variety of dppz complexes of Ru derivatized with alkyl ether chains of various lengths and used confocal laser scanning microscopy to study their subcellular localization in CHO-K1 cells. 84 Using various RNA and membrane-specific dyes, they found, perhaps not surprisingly, that the least lipophilic compound localized in the nucleus, while the most lipophilic localized in membranes.…”
Section: Subcellular Localization Of the Metal Complexmentioning
confidence: 97%
“…Interestingly, the length of the alkyl ether chain influences the nucleic acid binding properties of the three metal complexes. The complex of intermediate lipophilicity accumulates in RNA-rich nucleoli, and in vitro studies confirmed that it has higher binding affinity for rRNA vs CT-DNA [152]. The authors suggest that the increased lipophylicity of the complex may account for this binding preference.…”
Section: Rna Binding Properties Of Ruthenium(ii) Complexes Containingmentioning
confidence: 89%
“…15b) [152]. It is known that ligand modifications influence cellular uptake and accumulation, and also nucleic acid binding properties of this class of compounds [6,9,152,154,155]. Interestingly, the length of the alkyl ether chain influences the nucleic acid binding properties of the three metal complexes.…”
Section: Rna Binding Properties Of Ruthenium(ii) Complexes Containingmentioning
confidence: 99%
See 1 more Smart Citation